The Oldest Trick in the Book: Borges and the "Rhetoric of Immediacy'' - James Winchell (Studies in 20th & 21st Century Literature, 1993)
In his most "philosophical'' texts, Jorge Luis Borges paradoxically posits the act of reading as the scene of affectively "immediate" experience: his reader reads a reader reading (ad infinitum). This sort of hyper-meditated, specular imitation actually comes to mirror the substantive preoccupation of the "philosophical" text itself. Borges thereby breaks down what Theodor Adorno calls "concept fetishism'' by making mimesis his textual concept. Given Italo Calvino's claim for the novelty of "The Approach to Al-Mu'tasim" in relation to modern genres, I propose a two-fold thesis: first, that this typically Borgesian narrative juxtaposes concept and mimesis (a traditional philosophical antinomy) and then subverts the difference between them as a mediation of immediacy itself. He creates thereby a second-level "rhetoric of immediacy." Borges thus arrives at a re-inscription of the kind of narrative technique upon which traditional texts, even texts that form a part of a sacred canon, operate. The drama and rhetoric of immediacy exploited by Borges—and what is allegory, if not a "rhetorical drama''?—far from amounting to the last innovation of modem forms, as Calvino claims, might more accurately be called the oldest trick of presence in the book of absence.
Keywords: Argentine literature; Borges; philosophy; ad infinitum; hyper-mediation; Theodor Adorno; concept fetishism; memisis; mediation